EFFECT OF UMMB FEEDING ON BLOOD GLUCOSE AND FREE FATTY ACID LEVELS IN POSTPARTUM BUFFALOES - Kumar, S; Verma, H K; Gandotra , V K; Kasrija , Rajesh (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
A study was undertaken to observe the variation in blood glucose and free fatty acid levels in postpartum buffaloes during winter and summer seasons. Twenty seven freshly calved buffaloes were selected and they were divided into two groups. In the experimental group, UMMB was supplemented and the animals were observed for the manifestation of first behavioral estrus up to 60 days postpartum. There was non significant (P = 0.05) variation of blood glucose between experimental and control groups during both the seasons. However, the plasma free fatty acids were significantly (P= 0.05) higher in summer season and there was no significant variation of plasma free fatty acid levels by UMMB feeding during both the seasons.
Keywords: UMMB; Biochemical; blood glucose; free fatty acid; buffalo